2021
DOI: 10.1177/00208728211067158
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 feminist framework and biopsychosocial-spiritual perspective for social workers and mental health practitioners to manage violence, abuse, and trauma against children, women, BIPOC, and LGBTQIA+ during and post-COVID-19

Abstract: This article explains the integrated implementation of a COVID-19 Feminist Framework (CFF) and biopsychosocial-spiritual perspective (BPSS-P) on the inclusive equitability of social service providers, practitioners, and policy-developers on global platforms. Mechanisms of CFF and BPSS-P entail the process to address/mitigate institutional inequities, mental health issues, violation of human rights, race/sex/gender-based violence, abuse, and trauma amid COVID-19. This discourse is about raising consciousness, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Productive performance examination framework provides satisfaction level of employees through their diligent work, vigilant reasoning and association with the organisation. 29 Another finding of current study's indicated that the performance appraisal is a measure to enhance and boost the performance of employees and pave a way for career opportunity, promotion and further rewards. Previous research has indicated the mediating relationship between performance appraisal and perceived job satisfaction of healthcare sector employees.…”
Section: Seb B T Pmentioning
confidence: 78%
See 1 more Smart Citation
“…Productive performance examination framework provides satisfaction level of employees through their diligent work, vigilant reasoning and association with the organisation. 29 Another finding of current study's indicated that the performance appraisal is a measure to enhance and boost the performance of employees and pave a way for career opportunity, promotion and further rewards. Previous research has indicated the mediating relationship between performance appraisal and perceived job satisfaction of healthcare sector employees.…”
Section: Seb B T Pmentioning
confidence: 78%
“…Performance appraisal activities can divulge the employees' work improvement. Productive performance examination framework provides satisfaction level of employees through their diligent work, vigilant reasoning and association with the organisation 29 …”
Section: Discussionmentioning
confidence: 99%
“…During and post COVID-19, women will need safety and solidarity behind and beyond the walls as well. 75 Feminism is the opposition of patriarchal system’s way of reinforcing binary and black-and-white constructs—perceived good feminism/bad feminism where good constitutes the demand of health care and education rights and bad constitutes marital, sexual, and bodily autonomy, political/legal rights, economic equality, reproductive rights, and minority’s rights. Feminism delayed is feminism denied.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 lockdown, victims of intimate partner violence (IPV) are forced to remain with abusive partners and away from help, which has further exacerbated domestic violence. 1 COVID-19 quarantine exposed underlying inequalities such as domestic/intimate partner violence, abuse, and trauma (DIVAT) and gender-based violence, which consequentially perpetuate psychological trauma in women. Disconnection from institutional, medical, and informal support networks makes IPV, more than ever, life-threatening.…”
Section: Introductionmentioning
confidence: 99%